2016
DOI: 10.1371/journal.pone.0152409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Texting Language on Grammar and Executive Functions in Primary School Children

Abstract: When sending text messages on their mobile phone to friends, children often use a special type of register, which is called textese. This register allows the omission of words and the use of textisms: instances of non-standard written language such as 4ever (forever). Previous studies have shown that textese has a positive effect on children’s literacy abilities. In addition, it is possible that children’s grammar system is affected by textese as well, as grammar rules are often transgressed in this register. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Nothing in the results indicates that texting language improves students' writing, nor is there any evidence that shows otherwise. However, the results from Dijk et al's (2016) study show that texting language is linked with students' general grammar performance because learners analyse sentences to decide what to drop or use in which context. As such, they 'constantly train their grammatical knowledge and strengthen their grammatical performance' (Dijk et al, 2016: 17).…”
Section: Findings and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nothing in the results indicates that texting language improves students' writing, nor is there any evidence that shows otherwise. However, the results from Dijk et al's (2016) study show that texting language is linked with students' general grammar performance because learners analyse sentences to decide what to drop or use in which context. As such, they 'constantly train their grammatical knowledge and strengthen their grammatical performance' (Dijk et al, 2016: 17).…”
Section: Findings and Discussionmentioning
confidence: 94%
“…We further hypothesised that frequent SMS users may develop an improved skill in writing. This premise was based on previous research that has shown that texting improves learners' performance in vocabulary and grammar (Dijk et al, 2016) and literacy development (Verheijen, 2013).…”
Section: The Present Studymentioning
confidence: 99%
“…How original are each textim?). Moreover, it will be necessary in another study to add some standardized measures of executive functions (e.g., flexibility, inhibition and processing speed) as well as some control for the texters' level of vocabulary (Anderson & Reidy, 2012;Miyake & Friedman, 2012;Van Dijk, Van Witteloostuijn, Vasić, Avrutin, & Blom, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…But the process of normalization would be a little inconvenient for users of chatting software because they prioritize the practicality than the structure. Belal (2014) objected that bad spelling from social media provides negative influence since incorrect grammar and sentence structure in students writing can be affected by SNS. Nonetheless, SNS also has beneficial impact which was confirmed by Belal that SNS may help the students and also teacher to exchange ideas and to formulate group discussion.…”
Section: The Debate About the Netizen Spelling Systemmentioning
confidence: 99%